Level of Self-confidence among Female Students of Hail University in Saudi Arabia in Relationship with some Variables - Wedad Mohammad Saleh Alkferi (University of Science and Technology, Yemen, 2017)
This study aimed to detect the level of self-confidence among female students of Hail University, and whether there were significant differences at the level of the students' self-confidence attributed to the variables of age and specialization. The study sample, which was randomly selected, consisted of 802 students from various disciplines at the university (medicine, engineering, psychology, and Islamic culture) enrolled for the second semester of the academic year (2015/2016). To achieve the objectives of the study a confidence Scale developed by Kawasmeh and Farah (1996). The scale was checked for its validity and reliability. The statistical package SPSS was used to extract the results. Results of the study revealed a low level of self-confidence for the students of the university, whereas there were no statistically significant differences due to the variables of age and specialization. Keywords: Self-confidence, Students of Hail University, Saudi Arabia, Some variables.